Enhancement of ethanol sensing properties by impregnating platinum on surface of ZnO tetrapods - N. Hongsith (2018)
ZnO tetrapods with a cross-sectional size of about 200-1000 nm were synthesized via an oxidation reaction technique. The sensors based on ZnO tetrapods and platinum impregnated ZnO tetrapods were fabricated and investigated for ethanol sensing properties. The gas sensing properties of the sensors were investigated for ethanol concentration of 50-1000 ppm at different operating temperatures. It was found that the sensitivities of platinum impregnated ZnO tetrapod sensors were higher than that of pure ZnO tetrapod sensors. The enhancement of sensitivity due to platinum impregnation to ZnO tetrapods may be explained either by an increase of adsorbed oxygen density or an increase of reaction rate coefficient in a rate equation for an ethanol adsorption reaction on the ZnO surface. Also, the slope value of the plot between log(S' - 1) and log C suggested that adsorbed oxygen ion species at the surface of the platinum impregnated ZnO tetrapods was 02-which was the same as pure ZnO tetrapods. Finally, these results have an important implication for a development of ethanol sensors based on metal oxide semiconductors for alcohol breath analyzers. © 2009 IEEE.